Analisis Kinerja Keuangan Perusahaan pada PT. Wilmar Cahaya Indonesia Tbk di Bursa Efek Indonesia - Tasmita, Yuni Nuardi (Innovative: Journal Of Social Science Research, 2025)
This study aims to emphasize the importance of conducting a financial performance analysis of the company at PT. Wilmar Cahaya Indonesia Tbk on the Indonesia Stock Exchange. The analysis method in this study uses a quantitative descriptive method using financial report data from PT. Wilmar Cahaya Indonesia Tbk. using ratio analysis in the form of liquidity ratio, solvency ratio, activity ratio, and profitability ratio. The results of the research on the liquidity ratio of PT. Wilmar Cahaya Indonesia Tbk's financial performance using the current ratio, the highest current ratio value occurred in 2022, which was 995.42% and the lowest current ratio value occurred in 2020, which was 466.27%. Solvency ratio, where the lowest Debt To Asset Ratio value occurred in 2022, which was 9.79% and the highest Debt To Asset Ratio value occurred in 2020, which was 19.53%. And the Debt To Equity Ratio obtained from the average calculation for 4 years was 20.15%, while the lowest debt to equity ratio value occurred in 2022, which was 10.85% and the highest debt to equity ratio value occurred in 2020, which was 24.27%. Activity ratios using the ratio Receivables turnover ratio, where the highest receivables turnover ratio occurred in 2021, which was 9.52 times and the lowest receivables turnover ratio occurred in 2022, which was 7.28 times. Fixed asset turnover ratio, where the highest fixed asset turnover ratio occurred in 2022, which was 22.81% and the lowest fixed asset turnover ratio occurred in 2019, which was 15.98 times. And Total turnover ratio, where the highest total asset turnover ratio occurred in 2022, which was 3.58 times and the lowest total asset turnover ratio occurred in 2019, which was 2.24 times. Profitability ratio. where the highest Return On Asset occurred in 2019, which was 15.47% and the lowest Return On Asset occurred in 2021, which was 11.02%. And the highest Return On Equity occurred in 2019, which was 19.05% and the lowest Return On Equity occurred in 2021, which was 13.48%.